Coordination in United Nations peacebuilding: A theory-guided approach; Koordination in VN-Friedensmissionen: Eine theoriegeleitete Herangehensweise - Anna Herrhausen (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2007)
Coordination between different United Nations (UN) departments, funds, agencies, and programmes has become an issue of increasing concern for scholars and practitioners alike. With the United Nations taking on ever more ambitious roles in countries emerging from conflict ; no single unit or agency can master the task of post-conflict reconstruction ; also known as peacebuilding ; alone; instead ; a concerted effort is called for. Recent efforts at reorganizing the way the United Nations works in peacebuilding missions have not yielded the desired results of achieving a more coherent ; and in that way more efficient and more effective UN presence. In order to offer fresh inputs for the debate ; this paper looks at the issue of coordination from a theoretical perspective. Informed by organization theory ; a framework for interorganizational coordination is developed and then applied to the United Nations and peacebuilding. The main finding is that in order to improve interorganizational coordination and in lieu of trying to become one streamlined hierarchical organization ; the United Nations should acknowledge its network character and cultivate those social and structural control mechanisms which facilitate coordination in networks. – – Die Koordination zwischen verschiedenen Einheiten des Systems der Vereinten Nationen (VN) hat in den letzten Jahren sowohl für Praktiker als auch für Akademiker zunehmend an Bedeutung gewonnen. Da die Vereinten Nationen immer ambitioniertere Aufgaben der Konfliktnachsorge ; der Demokratisierung und des Wiederaufbaus in Krisenregionen übernehmen ; wird der Ruf nach einem koordinierten Vorgehen immer lauter – denn keine einzelne VN Unterorganisation kann die Fülle der Aufgaben allein bewältigen. Trotzdem haben die Bemühungen der letzten Jahre hin zu mehr Koordination und Integration bisher nicht die erhofften Ergebnisse gezeigt. Dieses Papier möchte zur aktuellen Debatte beisteuern ; indem es zuerst das Thema ,,Koordination“ von einem theoretischen Blickwinkel aus beleuchtet. Basierend auf den Erkenntnissen der Organisationslehre wird ein theoretisches Modell der Koordination entwickelt – dieses wird dann auf die Vereinten Nationen als Unternehmer von Friedensmissionen angewandt. Haupterkenntnis ist hierbei ; dass ; um interorganisationelle Koordination innerhalb der Vereinten Nationen zu verbessern ; die sozialen und strukturellen Koordinationsmechanismen gestärkt werden sollten ; die dem netzwerkartigen Charakter des Systems entsprechen – anstatt weiterhin zu versuchen ; über das ganze System hinweg eine straffe Hierarchie durchzusetzen.
Keywords: 300; coordination; multidimensionality; organization theory; peacebuilding; Koordination; Multidimensionalität; Organisationslehre; Friedenssicherung